Clinical Aspects of Bacterial Distribution and Antibiotic Resistance in the Reproductive System of Equids - Panagiota Tyrnenopoulou; George C. Fthenakis (MDPI AG, 2023)
Antibiotic administration is a standard therapeutic practice for the treatment of reproductive disorders of equids. This might lead to undesirable microbial imbalance and could favour the acquisition of antibiotic resistance. Therefore, it is imperative for clinicians to understand patterns of antibiotic resistance when considering and developing treatment regimes. Continued engagement of clinicians with novel alternative approaches to treat reproductive infections would be essential in order to address this rising threat within the One Health perspective. The objectives of the present review were to present the bacterial infections in the reproductive system of equids (horses, donkeys), to upraise the literature related to the issue of antibiotic resistance of bacteria causing these infections and to discuss the topic from a clinical perspective. Initially, the review summarised the various infections of the reproductive system of equids (genital system of females, genital system of males, mammary glands) and the causal bacteria, providing relevant information about horses and donkeys. Subsequently, the clinical therapeutics of these infections were presented, taking into account the significance of antibiotic resistance of bacteria as a limiting factor in treating the infections. Finally, approaches to circumvent antibiotic resistance in clinical settings were summarized. It was concluded that awareness regarding antibiotic resistance in equine reproductive medicine would increase, as we would recognise the multifaceted problem of resistance. Actions and initiatives within the One Health approach, minimizing the potential dissemination of resistant strains to humans and to the environment, with specific applications in medicine of equids should be appropriately instituted internationally.